Analysis Of Water Resources Sustainability in the Batang Kuranji Basin, Padang with The Nedbør Afstrømnings Model (NAM) - Alqadri Asri Putra; Eri Gas Ekaputra; Azwar Rasyidin (Universitas Muhammadiyah Sidoarjo, 2021)
The Batang Kuranji watershed is an area that plays a vital role in the water resources preservation and conservation in Padang city. However, recently the sustainability of these water resources has suffered hydrologically, marked by a sharp fluctuating flood discharge. This study aims to measure the water resources sustainability in the Batang Kuranji watershed. The method used in this research is Nedbør Afstrømnings Model (NAM) modeling and an integrated approach. The results of NAM showed that the most prominent parameter values ​​are TIF (0.9), TG (0.965), CK1 (0.23), and CK2 (1.1), which indicate an infiltration transformation in this watershed. The integrated analysis showed that deforestation and population growth are the main factors for this issue, and the land-use conversion also affected these problems. Reducing the population growth rate, evaluating the urban development, reforestation, and improving water infrastructure along rivers-side will reduce the risk of watershed damage and maintain its sustainability.